2016
DOI: 10.1371/journal.pone.0151593
|View full text |Cite
|
Sign up to set email alerts
|

Aging and Sensory Substitution in a Virtual Navigation Task

Abstract: Virtual environments are becoming ubiquitous, and used in a variety of contexts–from entertainment to training and rehabilitation. Recently, technology for making them more accessible to blind or visually impaired users has been developed, by using sound to represent visual information. The ability of older individuals to interpret these cues has not yet been studied. In this experiment, we studied the effects of age and sensory modality (visual or auditory) on navigation through a virtual maze. We added a lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 44 publications
3
16
1
Order By: Relevance
“…Blindfolded participants were able to generate a representation of space using SSD vibration information and adopt a strategy that is similar to the one used during visual navigation, as has been shown in previous work [ 10 ]. The finding that movement times and velocity corrections were greater under SSD guidance than under vision is consistent with results from a recent study [ 27 ] which showed that the number of pauses and time taken to complete a trial when navigating through virtual mazes were greater when using an SSD than when using vision. Next, we discuss possible interpretations of how participants use sensory information from a substituted modality to navigate around an obstacle.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Blindfolded participants were able to generate a representation of space using SSD vibration information and adopt a strategy that is similar to the one used during visual navigation, as has been shown in previous work [ 10 ]. The finding that movement times and velocity corrections were greater under SSD guidance than under vision is consistent with results from a recent study [ 27 ] which showed that the number of pauses and time taken to complete a trial when navigating through virtual mazes were greater when using an SSD than when using vision. Next, we discuss possible interpretations of how participants use sensory information from a substituted modality to navigate around an obstacle.…”
Section: Discussionsupporting
confidence: 90%
“…Although SSDs can be highly useful as a navigation aid, collisions do sometimes occur. Levy-Tzedek et al [ 27 ] reported that the rate of collisions was higher using the Eyecane SSD than using vision to navigate in virtual mazes. Veraart et al [ 28 ] reported that binocularly blinded cats were able to use echoic SSD information to assess depth in a jumping task and to avoid obstacles when moving through a maze.…”
Section: Introductionmentioning
confidence: 99%
“…‘Virtual environments’, which have recently been successfully used for training with sensory substitution devices (Maidenbaum et al 2013, Maidenbaum et al 2014, Chebat et al 2015, Levy-Tzedek et al 2016, Maidenbaum et al 2016), offer an elegant way to solve many of these difficulties. Within the VR context it is easy to generate a varied stimulus set of objects or environments.…”
Section: Perceptual Learningmentioning
confidence: 99%
“…So even if brain training evidence is scarce in normal populations, the implications may not be as severe for situations involving dysfunctional senses. And there is indeed promising evidence regarding the use of virtual training environments such as virtual mazes or video-games in sensory substitution ( Lahav, Schloerb, & Srinivasan; 2012 ; Merabet et al, 2012 ; Levy-Tzedek et al, 2016 ; Maidenbaum et al, 2014c ; Maidenbaum & Amedi, 2015 ).…”
Section: Key General Considerations For Sensory Substitutionmentioning
confidence: 99%